2002
DOI: 10.1038/sj.ijo.0801853
|View full text |Cite
|
Sign up to set email alerts
|

Weight-teasing among adolescents: correlations with weight status and disordered eating behaviors

Abstract: OBJECTIVES: This study aimed to assess the prevalence of perceived weight-teasing and associations with unhealthy weightcontrol behaviors and binge eating in a population-based sample of youth. Particular focus was placed on overweight youth, who may be most vulnerable to weight-teasing. METHODS: The study population included 4746 adolescents from St Paul=Minneapolis public schools who completed surveys and anthropometric measurements as part of Project EAT, a population-based study of eating patterns and weig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

48
525
7
17

Year Published

2003
2003
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 614 publications
(607 citation statements)
references
References 26 publications
48
525
7
17
Order By: Relevance
“…Previous studies have indicated that body dissatisfaction and psychological functioning may contribute to obesity and negative health outcomes (Durso, Latner, & Ciao, 2016;Muennig, Jia, Lee, & Lubetkin, 2008;Wilson, Latner, & Hayashi, 2013). Our data showed no gender differences in WB contrary to other studies, where girls reported more WB than boys (Eisenberg, Neumark-Sztainer, Haines, & Wall, 2006;Neumark-Sztainer et al, 2002). In addition to elucidating gender differences with WB, future researchers should focus on exploring the types of bias and the perceptions and internationalization of bias which may be more crucial than the amount of bias experienced in this population (Lewis et al, 2011).…”
Section: Discussioncontrasting
confidence: 64%
“…Previous studies have indicated that body dissatisfaction and psychological functioning may contribute to obesity and negative health outcomes (Durso, Latner, & Ciao, 2016;Muennig, Jia, Lee, & Lubetkin, 2008;Wilson, Latner, & Hayashi, 2013). Our data showed no gender differences in WB contrary to other studies, where girls reported more WB than boys (Eisenberg, Neumark-Sztainer, Haines, & Wall, 2006;Neumark-Sztainer et al, 2002). In addition to elucidating gender differences with WB, future researchers should focus on exploring the types of bias and the perceptions and internationalization of bias which may be more crucial than the amount of bias experienced in this population (Lewis et al, 2011).…”
Section: Discussioncontrasting
confidence: 64%
“…Furthermore, social functioning has been observed to be an area of difficulty for overweight children and adolescents, 30,31 and social support for eating and exercise was found to be a significant predictor of long-term weight loss in a 10-year follow-up of children treated for obesity. 32 Consequently, an intervention that targets both self-efficacy and social function may have particular benefit for overweight adolescents.…”
Section: Introductionmentioning
confidence: 97%
“…1,2 Weight bias occurs from employers, 3,4 health-care professionals, 5-9 educators [10][11][12] and even family members. 13 Its negative implications include impairments in psychological well-being [14][15] and physical health, such as avoiding preventive health-care services, 16 engaging in unhealthy eating patterns 13,[17][18][19] and avoiding physical activity. 18,[20][21][22] Despite evidence of weight bias documented in case studies, experimental work, treatment and convenience samples, limited information is available on the prevalence and patterns of weight discrimination in a nationally representative sample.…”
Section: Introductionmentioning
confidence: 99%
“…13 Its negative implications include impairments in psychological well-being [14][15] and physical health, such as avoiding preventive health-care services, 16 engaging in unhealthy eating patterns 13,[17][18][19] and avoiding physical activity. 18,[20][21][22] Despite evidence of weight bias documented in case studies, experimental work, treatment and convenience samples, limited information is available on the prevalence and patterns of weight discrimination in a nationally representative sample. Discrimination is distinct from prejudice and beliefs in that it refers to negative, unequal treatment of people because of their membership in a particular group.…”
Section: Introductionmentioning
confidence: 99%